Oral Health and Cognitive Decline: A Systematic Review of the Periodontitis–Alzheimer’s Connection - Angelo Michele Inchingolo; Alessio Danilo Inchingolo; Fabio Piras; Pasquale Avantario; Laura Ferrante; Gregorio Paduanelli; Francesco Inchingolo; Andrea Palermo; Gianna Dipalma; Massimo Corsalini (Applied Sciences, 2025)
Background: Alzheimer’s disease (AD), a neurodegenerative disorder characterized by cognitive decline, has been linked to systemic inflammation. Periodontal disease (PD), a chronic inflammatory condition, may contribute to neurodegeneration via microbial dysbiosis and inflammatory pathways. This systematic review explores the potential association between PD and AD, emphasizing microbial and systemic mechanisms. Materials and Methods: Following PRISMA guidelines, we searched PubMed, Scopus, and Web of Science for studies published between 2015 and 2024. The boolean keywords “Alzheimer” AND “parodont*” were used. The inclusion criteria focused on human studies evaluating salivary and blood biomarkers, as well as periodontal therapies. Data extraction adhered to the PICO framework, assessing study design, outcomes, and quality using the ROBINS-I tool (original 2016 version), as provided by the Cochrane Bias Methods Group. Results: Out of the 1244 articles screened, 19 studies met the inclusion criteria. Evidence indicates that periodontal pathogens, such as Porphyromonas gingivalis, promote neuroinflammation, amyloid-β aggregation, and brain atrophy. Elevated inflammatory markers and oral dysbiosis correlated with increased AD risk. Periodontal treatment demonstrated benefits in reducing systemic inflammation and stabilizing cognitive decline. Conclusion: The findings suggest a strong link between PD and AD through systemic inflammation and microbial invasion. Maintaining oral health may serve as a preventive strategy against cognitive decline, underscoring the need for integrated medical–dental care and further longitudinal research.